Measuring climate action readiness in maintaining ecological resilience using satellite imagery and field research in Garang Watershed, Central Java, Indonesia - BAMBANG SUDARMANTO; SURANTO SURANTO; SUNTORO SUNTORO; JOKO SUTRISNO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sudarmanto B, Suranto S, Suntoro S, Sutrisno J. 2023. Measuring climate action readiness in maintaining ecological resilience using satellite imagery and field research in Garang Watershed, Central Java, Indonesia. Biodiversitas 24: 2958-2974. The long-term viability of vegetation as a representation of land cover in a watershed is critical. However, more work is needed to develop vegetation management in the form of a climate action model that considers the existence of ecological and social values as a unified system, particularly in times of climate change. Moran's Index measurements and statistical correlation analysis were employed in this study to quantify geographical patterns. These measurements provide real-world judgment in developing aggressive climate response scenarios. Ecological values were derived from shifting vegetation trend indices due to mutual interaction between living beings that build a life cycle in harmony with the environment. Meanwhile, social values are determined by assessing individual internal factors such as attitudes, knowledge, and responses and external factors represented by local government institutions. The findings reveal that the distribution of residents and residential areas is dispersed. With a high confidence level, a linear index declines with R2 = 0.5872 for inhabitants and R2 = 0.9171 for residential areas. In the dry season, there is a significant relationship between the spatial pattern of vegetation indices and the inhabitant's index. The community's knowledge and attitudes considerably impact changes in vegetation indices, particularly during the rainy season, with R2 = 0.207 for SAVI and 0.232 for NDVI. Community readiness values, which elaborate on knowledge, attitudes, responses, and the role of external institutions, show that community readiness in the upstream area of the watershed, specifically in the Kendal District, is in the best position, with a value of 6.627976. On the contrary, the Semarang District, the upstream area, has the lowest value of 4.257092.